The impact of sustainable development indicators on the consumption of renewable energy in the Kingdom of Saudi Arabia - Nasrulddin, Vivian Mohammed Saleh; Abo Madini, Khadijah Mohammed; Al-Bishr, Somaia Abdulrahman Nasir; Al-Zahrani, Shrooq Mohammed (Journal of Economic, Administrative and Legal Sciences, 2023)
The study aimed to measure the impact of a set of sustainable development indicators on renewable energy consumption in the KSA, during the period (1990-2020), using the ARDL model, to measure the relationship between renewable energy consumption as a dependent variable and sustainable development indicators as independent variables, in both the short and the long-term. Using the E-views statistical program, the study concluded, as expected: that the relationship between renewable energy consumption and foreign direct investment is positive in the short-term, and the relationship between renewable energy consumption and energy depletion rate is inverse in both terms. In addition, there has been a long-term inverse relationship between renewable energy consumption and per capita CO2 emissions. Contrary to what is expected: there was an inverse relationship between the consumption of renewable energy and the per capita GDP in the short-term, and the relationship was positive between the consumption of renewable energy and the unemployment rate in both terms. In addition, there was a short-term positive relationship between renewable energy consumption and per capita CO2 emissions. Finally, the results concluded that foreign direct investment and per capita GDP did not affect the consumption of renewable energy in the long-term.
Keywords: Sustainable development; renewable energy; energy depletion